THE SIGNIFICANCE OF ASSESSMENT OF TOP MANAGERS ON THE ISSUE OF IMPLEMENTATION INTERNAL AUDITS IN BUSINESS AND MANAGEMENT OF MEDIUM-SIZED COMPANIES, THE EXAMPLE OF THE REPUBLIC OF SERBIA (Heritage, 2025)
Modern business management requires top management to implement innovative solutions such as the implementation of internal audit in the business of the company. One of the possible ways to measure the effect of such management is presented in the author's work by evaluating the impact of the introduction of internal audit before and after the implementation of internal audit in the company's operations. We discovered that there are important differences in the evaluation of top management regarding the introduction of internal audit as a basis for real financial reporting, because the obtained values are significant (p=.000) in relation to the introduction of internal audit both before and after the introduction of internal audit in regular business operations medium-sized enterprises in the Republic of Serbia. The goal of the author's research was to present a possible contribution to real future accounting based on the introduction of internal audit into real business processes, that can substantially contribute to the improvement of overall business results. Keywords: Internal Audit, Business, Management by Top Management, Company.
Keywords: Internal Audit, Business, Management by Top Management, Company